Дослідження у м. Володимир-Волинський у 2009 р. - Златогорський, О.Є.; Панишко, С.Д. (Археологічні дослідження в Україні, 2010)
Information on excavations on the territory of a circuitous city of mediaeval Volodymyr in 2009 is provided. Under thick layers certain objects were discovered, particularly a well.